Tracing the Threads: Spirituality, Transformation, and Religious Doubt Within the Field of Adult Education - MacKenzie, Michael D. (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2022)
While spirituality has emerged as a topic of interest in adult education, much of the current scholarship considers spirituality as distinct from religion. This literature review questions those conclusions, including the use of theistic terminology to describe a concept (spirituality) that many posit is non-theistic. Spirituality is also considered in terms of transformative learning theory and spiritually centred transformation, specifically as a type of non-cognitive transformation. In this way, spirituality is placed alongside other types of affective or emotionally based ways of knowing, learning, and transforming. Finally, experiences of religious doubt—defined as dissonance or uncertainty in one’s religious and faith beliefs—are identified as potential catalysts that launch the transformative learning process. The review concludes by identifying the need for more research into the intersections of religious doubt and transformative learning in terms of what this research might tell us about the nature of both doubt and transformation.